Entanglement harvesting with moving mirrors - Wan Cong (Journal of High Energy Physics, 2019)
Abstract We study the phenomenon of entanglement extraction from the vacuum of a massless scalar field in (1 + 1) dimensional spacetime in presence of a moving Dirichlet boundary condition, i.e. mirror spacetime, using two inertial Unruh-DeWitt detectors. We consider a variety of non-trivial trajectories for these accelerating mirrors and find (1) an entanglement inhibition phenomenon similar to that recently seen for black holes, as well as (2) trajectory-independent entanglement enhancement in some regimes. We show that the qualitative result obtained is the same for both linear and derivative couplings of the detector with the field.